PENGEMBANGAN KEMAMPUAN KOGNITIF MURID SEKOLAH'DASAR MELALUI PENDIDIKAN JASMANI - Pamuji Sukoco (LPMPP Universitas Negeri Yogyakarta, 2008)
The elementary school students are at a stage in need of an environmentconducive for their development. Physical education can enhance cognitive abilitythrough physical activities in the learning process. The teaching learning process inPhysicalEducation should be designed with motoric experience that developsmotoric perception, drives social interaction, and stimulates cognitive ability. Thelearning approach should use games and stimulate problem solving. The studentsshould get the opportunity to think logically and creatively and develop theirattention and memory